A transition-metal-free, one-pot procedure for the synthesis of α, β-epoxy ketones by oxidative coupling of alkenes and aldehydes via base catalysis. Issue 6 (10th December 2014) - Ke, Qingping; Zhang, Bingyan; Hu, Bolun; Jin, Yangxin; Lu, Guanzhong
Abstract : A new strategy for the synthesis of epoxides is presented. Abstract : A new strategy for the synthesis of epoxides is presented. This process allows the direct synthesis of epoxides from alkenes and aldehydes through C–H functionalization and C–C/C–O bond formation.